Ordeal by Dinner: US Diplomats and Food Culture in the Russian Empire - Paulson, Svetlana (Journal of Russian American Studies, 2023)
This article examines the encounters of US diplomats with food culture in the Russian Empire. Understanding local traditions associated with food was essential for diplomats who had to attend and host various receptions and formal dinners. Based on diaries, letters, and memoirs, the author argues that the Americans - representatives of a republic - found an immersion into food culture of an autocratic state, where the extremely elaborate rituals of food consumption were a part of a social-distinction signaling system, challenging. However, they learned to navigate all the nuances, representing their own country and traditions with dignity. Their observations about food in the capital of the Tsars reveal valuable details about the inner workings of the Russian Empire.